KEPUASAN PETANI TERHADAP LAYANAN PASAR LELANG CABAI SIDO DADI DI KABUPATEN KULON PROGO - Rahmi Dwi Agustin; Agus Dwi Nugroho; Masyhuri Masyhuri (Universitas Sebelas Maret, 2021)
One of the Sido Dadi auction market weaknesses is delay payment system to farmers. This system is done by waiting for payment from the merchant if the chili has been completely sold. This situation causes farmers to be dissatisfied with the auction market services. This study intended to determine the level of farmer’s satisfaction to the Sido Dadi auction market services and its determinant factors. This research was conducted at the Sido Dadi auction market because it was the first auction market in Galur District, Kulon Progo Regency, Yogyakarta Province. The number of respondents was 60 farmers chosen by purposive sampling. The Customer Satisfaction Index (CSI) and regression used to analyze the data. The results showed that farmers were satisfied with the auction market services. The determinant factors of farmer’s satisfaction are age, education level, and land area. Farmer satisfaction is in line with increasing of farmers’ age but in contrast to education and the farmer's land area. The Sido Dadi auction market needs to use of the contribution funds to complement infrastructure and held human resource development training. The auction market also needs to have a service Standard Operating Procedures for farmers. In addition, the local government officer needs to intensively provide service management training for auction market managers.